Targeting TGF-β signaling in the multiple myeloma microenvironment: Steering CARs and T cells in the right direction - Rana, Priyanka S.; Soler, David C.; Kort, Jeries; Driscoll, James J. (Frontiers in Cell and Developmental Biology, 2022)
Multiple myeloma (MM) remains a lethal hematologic cancer characterized by the expansion of transformed plasma cells within the permissive bone marrow (BM) milieu. The emergence of relapsed and/or refractory MM (RRMM) is provoked through clonal evolution of malignant plasma cells that harbor genomic, metabolic and proteomic perturbations. For most patients, relapsed disease remains a major cause of overall mortality. Transforming growth factors (TGFs) have pleiotropic effects that regulate myelomagenesis as well as the emergence of drug resistance. Moreover, TGF-β modulates numerous cell types present with the tumor microenvironment, including many immune cell types. While numerous agents have been FDA-approved over the past 2 decades and significantly expanded the treatment options available for MM patients, the molecular mechanisms responsible for drug resistance remain elusive. Multiple myeloma is uniformly preceded by a premalignant state, monoclonal gammopathy of unknown significance, and both conditions are associated with progressive deregulation in host immunity characterized by reduced T cell, natural killer (NK) cell and antigen-presenting dendritic cell (DC) activity. TGF-β promotes myelomagenesis as well as intrinsic drug resistance by repressing anti-myeloma immunity to promote tolerance, drug resistance and disease progression. Hence, repression of TGF-β signaling is a prerequisite to enhance the efficacy of current and future immunotherapeutics. Novel strategies that incorporate T cells that have been modified to express chimeric antigen receptor (CARs), T cell receptors (TCRs) and bispecific T cell engagers (BiTEs) offer promise to block TGF-β signaling, overcome chemoresistance and enhance anti-myeloma immunity. Here, we describe the effects of TGF-β signaling on immune cell effectors in the bone marrow and emerging strategies to overcome TGF-β-mediated myeloma growth, drug resistance and survival.